Aromatic heterocyclic resin : precursor for carbon materials and high temperature foams - Liu, Ming (2012)
Phthalonitrile based polymers have been intensively and persistently studied over the past few decades due to their potential as high temperature (HT) resistant thermoset. All studies so far emphasised on the resin formulation as HT matrices. This study focused on understanding the detailed structural formation responsible for the superior thermal properties of resorcinol-based phthalonitrile (RPh) polymer and extending its applications as organic precursors for carbon materials and resin for ultra-low density HT foams.